Translated Chinese as a legal language in Hong Kong legislation - Chan, Clara (The Journal of Specialised Translation, 2007)
The main purpose of this study is to establish the properties of translated Hong Kong Chinese as a language of law, and suggest ways to improve the lengthened and complicated sentence structures that result from the influence of the Western legal genre, in order to create a more user-friendly form of technical Chinese and strengthen its effective use for legal purposes.  It is widely and traditionally recognised that the translator of legal statutes is inclined to use a literal and faithful approach to translation, in order to minimize the loss of original meaning and reproduce the full legal effects of the legislation. The adoption of such an approach naturally results in the widespread preservation of the linguistic and cultural features of the original legal texts. This paper examines nine linguistic patterns in the Chinese version of the Sale of Goods Ordinance that may be deemed "Europeanised", of which five are either unexplored or little explored.